181 Comparison of Synthetic Mesh Erosion and Chronic Pain Rates After Surgery for Pelvic Organ Prolapse and Stress Urinary Incontinence: A Systematic Review. (4th May 2021) - MacCraith, E; Cunnane, E; Joyce, M; Forde, J; O'Brien, F; Davis, N
Abstract: Background: The aim of this study is to systematically compare rates of erosion and chronic pain after mesh insertion for pelvic organ prolapse (POP) and stress urinary incontinence (SUI) surgery. Method: A systematic electronic search was performed on studies that evaluated the incidence of erosion and chronic pain after mesh insertion for POP or SUI. The primary outcome measurement was to compare mesh erosion and chronic pain rates for POP and SUI surgery. Results: Twenty-six studies on 292, 606 patients ( n = 9077 for POP surgery and n = 283529 for SUI surgery) met inclusion criteria. The POP group were older (p < 0.0001) and had a lower BMI (p < 0.0001). Mesh erosion rates were significantly greater in the POP group compared to the SUI group (4% versus 1.9%) [OR 2.13; 95% CI 1.91-2.37; p < 0.0001]. The incidence of chronic pain was significantly greater in the POP group compared to the SUI group (6.7% versus 0.6%) [OR 11.02; 95% CI 8.15-14.9; p < 0.0001]. Conclusions: The risk of mesh erosion and chronic pain is significantly higher after surgery for POP compared to SUI. Since a higher volume of mesh is typically used for POP surgery this supports evidence for a dose-response relationship between the volume of mesh used and the erosion risk.